2017
DOI: 10.1016/j.ccell.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Promotes Gastric Tumorigenesis through Aberrant Cholinergic Signaling

Abstract: Summary Within the gastrointestinal stem cell niche, nerves help to regulate both normal and neoplastic stem cell dynamics. Here, we reveal the mechanisms underlying the cancer-nerve partnership. We find that Dclk1+ tuft cells and nerves are the main sources of acetylcholine (ACh) within the gastric mucosa. Cholinergic stimulation of the gastric epithelium induced nerve growth factor (NGF) expression, and in turn NGF overexpression within gastric epithelium expanded enteric nerves and promoted carcinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
399
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 389 publications
(441 citation statements)
references
References 63 publications
11
399
1
3
Order By: Relevance
“…Gastric stem cells are supported strongly by cholinergic signaling emanating in part from the vagus nerve acting through the muscarinic-3 receptor, and thus vagotomy markedly suppresses gastric cancer development in a variety of mouse models 85 . More recently, we have shown that both Dclk1 + tuft cells and nerves are important sources of acetylcholine within the gastric mucosa, and the cholinergic stimulation induces nerve growth factor expression, leading to an expansion of enteric nerves in the stomach, thus promoting gastric carcinogenesis 86 . Blockade of nerve growth factor signaling inhibits gastric tumor development, thus establishing the acetylcholine–nerve growth factor axis as a key component of the gastric cancer stem cell niche 86 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Gastric stem cells are supported strongly by cholinergic signaling emanating in part from the vagus nerve acting through the muscarinic-3 receptor, and thus vagotomy markedly suppresses gastric cancer development in a variety of mouse models 85 . More recently, we have shown that both Dclk1 + tuft cells and nerves are important sources of acetylcholine within the gastric mucosa, and the cholinergic stimulation induces nerve growth factor expression, leading to an expansion of enteric nerves in the stomach, thus promoting gastric carcinogenesis 86 . Blockade of nerve growth factor signaling inhibits gastric tumor development, thus establishing the acetylcholine–nerve growth factor axis as a key component of the gastric cancer stem cell niche 86 .…”
mentioning
confidence: 95%
“…An activated niche can facilitate the development of cancer derived from stem cells, and we and others have defined important cellular components of the gastric stem cell niche, including myofibroblasts, nerves, endothelial cells, innate lymphoid cells, pericytes, tuft cells, and hormone-producing cells20, 45, 57, 68, 85, 86, 87, 88 (Figure 2). Targeting these niche cells may be potentially useful in the inhibition of stem cell expansion and cancer development.…”
mentioning
confidence: 99%
“…Remarkably, Tf2-Cre;R29-NGF mice developed metaplasia and dysplasia by 8 months of age with CD44 + dysplastic cell expansion and intramucosal adenocarcinomas by 18 months. Ablation of Dclk1 + cells in this context led to the inhibition of epithelial proliferation and tumorigenesis in a M 3 R-dependent manner [22].…”
Section: Factors Sustaining Gastric Stem Cell Self-renewal and Multipmentioning
confidence: 98%
“…In stomach organoid models, coculture with neurons or treatment with pilocarpine, a cholinomimetic drug, increased organoid formation and the expression of Lgr5 and Cd44 stem cell markers, whereas the efects were reversed by botox treatment [21]. Another publication reported that Dclk1 + tuft cells and nerves, the main sources of acetylcholine in the gastric mucosa, induced nerve growth factor (NGF) secretion from epithelial cells that expand enteric nerves and promote carcinogenesis [22]. Remarkably, Tf2-Cre;R29-NGF mice developed metaplasia and dysplasia by 8 months of age with CD44 + dysplastic cell expansion and intramucosal adenocarcinomas by 18 months.…”
Section: Factors Sustaining Gastric Stem Cell Self-renewal and Multipmentioning
confidence: 99%
“…The authors of that study utilized a series of Dclk1-CreERT mouse models to show that acetylcholine from nerves and from Dclk1+ tuft cells, which acted as intermediary niche cells to coordinate neural input to help regulate subsequent stem cell activity, induced nerve growth factor in gastric epithelial cells; this in turn promoted neuron expansion and tumorigenesis [46] .…”
Section: Gcsc Regulation In the Tumor Microenvironmentmentioning
confidence: 99%